From refugees to legitimate minority?: Rohingya performing national belongings in Thailand - Jaehn, Miriam (SOJOURN, 2022)
Rohingya living in Thailand undergo a process of de facto integration that is based on a dual performance of nationality requiring the concealment of their Rohingya ethnicity in the public sphere. This dual performance of nationality is a result of their ‘double consciousness’ in displacement and aims to legitimatize the Rohingya as a minority group in and of Thailand that has its roots in Myanmar; and on which they base their claims to a rights-based inclusion in both countries. (Soujourn/GIGA)